2022
DOI: 10.1097/won.0000000000000880
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Self-managed Cooling Intervention for Pain and Physical Activity in Individuals With Recently Healed Chronic Venous Leg and Diabetic Foot Ulcers

Abstract: PURPOSE: This aim of this study was to evaluate the clinical efficacy of a self-managed cooling intervention in individuals with recently healed venous leg ulcers (VLUs) and diabetic foot ulcers (DFUs) on pain reduction and physical activity improvement. DESIGN: A 6-month longitudinal randomized controlled trial. SUBJECTS AND SETTING: The sample comprised 140 individuals with previously healed VLU and DFU who received care in 3 outpatient wound centers in the Southeastern region of the United States. Parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“… 26 Therefore, health care providers play an important role in wound management, including recommendations for self‐care measures after wound healing, adherence to the doctor's order, and frequently examine the healed site. 35 The studies in this review reported that inappropriate strategies and acute accidents were the two main causes of VLU recurrence. Therefore, an important step in the process of practicing self‐care is appraisal of patient's self‐treatment activities.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“… 26 Therefore, health care providers play an important role in wound management, including recommendations for self‐care measures after wound healing, adherence to the doctor's order, and frequently examine the healed site. 35 The studies in this review reported that inappropriate strategies and acute accidents were the two main causes of VLU recurrence. Therefore, an important step in the process of practicing self‐care is appraisal of patient's self‐treatment activities.…”
Section: Discussionmentioning
confidence: 89%
“…When patients actively participated in the self‐care management, they gained confidence; benefited from unnecessary and frequent visits to the hospital, and led to decrease the number of consultations 26 . Therefore, health care providers play an important role in wound management, including recommendations for self‐care measures after wound healing, adherence to the doctor's order, and frequently examine the healed site 35 . The studies in this review reported that inappropriate strategies and acute accidents were the two main causes of VLU recurrence.…”
Section: Discussionmentioning
confidence: 99%